A prospective study of comparison of scoring systems in trauma patients - Garg, Akshohini; Thakur, Digvijay Singh; Thakur, Bhavya; Purohit, Pulkit; Singh, Vikas; Chauhan, Nidhi (International Journal of Research in Medical Sciences, 2022)
Background: Trauma is a neglected area of the society. It is a health problem that is responsible for mortality and disability, predominantly among the young generation. Thereupon, the risk stratification of such patients become essential to avoid the mortality, for which various scoring systems are employed. Methods: A prospective observational study was conducted among the 300 polytrauma patients who presented in a tertiary care institute over a span of one and half year (March 2018 to December 2019). The severity of injuries of each patient was assessed using various scoring systems (GCS, RTS, AIS, ISS, NISS), and accordingly the outcome (mortality and hospital stay) was recorded. Results: Of the total 300 cases of polytrauma, the young men are most commonly afflicted with road traffic injuries as the leading cause. Most patients presented after a latent period of 2-8 hours since injury with predominantly accidental injuries. Total 21% mortality was observed in this study of which 5% patients succumbed early (<24 hours) despite all possible resuscitative efforts. Mortality was associated with lower GCS and RTS scores but higher ISS and NISS scores. Conclusions: All patients should have their GCS and RTS scores computed on admission along with the primary survey as they are good predictors of outcome and can predict salvageable patients from the non-salvageable ones. Both anatomical scores ISS and NISS can significantly predict the need for emergency life-saving surgery within 24 hours of admission.